2022
DOI: 10.1002/mde.3764
|View full text |Cite
|
Sign up to set email alerts
|

Are you resilient? Machine learning prediction of corporate rebound out of the Covid‐19 pandemic

Abstract: We use the Covid‐19 crisis to assess how four capability domains that traditionally support corporate performance (agility, innovation, ecosystem play and digitization) can also predict corporate resilience, among global firms. Our results are based on a blend of advanced machine learning techniques that capture the complementarities among capabilities. We confirm that dynamic capabilities boost recovery, but especially when linked with aggressive leadership posture, e.g. rebound is more likely when firms are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Initial research on multinational enterprises reveals that AI models can predict stock trends, thereby evaluating firms' corporate competitiveness (Zong & Wang, 2022). Similarly, AI models can predict corporate resilience, which may guide managers in developing dynamic capabilities to support their competitive advantage and create a portfolio of competencies to be used during a crisis (Bughin, 2023). Moreover, research on Finnish small and medium-sized firms has shown that AI models can predict the earliness of internationalization and international performance, thereby evaluating capability portfolios consisting of different firm resources such as managers' networking abilities, bricolage capabilities, and decision-making heuristics (Vuorio & Torkkeli, 2023).…”
Section: Learning Leads To Managerial Capabilitiesmentioning
confidence: 99%
“…Initial research on multinational enterprises reveals that AI models can predict stock trends, thereby evaluating firms' corporate competitiveness (Zong & Wang, 2022). Similarly, AI models can predict corporate resilience, which may guide managers in developing dynamic capabilities to support their competitive advantage and create a portfolio of competencies to be used during a crisis (Bughin, 2023). Moreover, research on Finnish small and medium-sized firms has shown that AI models can predict the earliness of internationalization and international performance, thereby evaluating capability portfolios consisting of different firm resources such as managers' networking abilities, bricolage capabilities, and decision-making heuristics (Vuorio & Torkkeli, 2023).…”
Section: Learning Leads To Managerial Capabilitiesmentioning
confidence: 99%
“…al. (2023),Bughin (2023),Ameen et al (2024),Castro-Lopez et al (2023),Zahoor et al (2023a, b), Bouguerra et al (2021), Babber and Mittal (2023Theoretical background in agility and organisational outcomes research The use of theory(ies) in agility-organisational outcomes research Number of publications Examples of publications No agility-related theory explicitly mentioned 109 Arslan et al (2024), Alkhatib and Momani (2023), Al-Shboul and Alsmairat (2023) Turi et al (2023) Singular theory 96 Akhtar et al (2022) Cha and Park (2023) Ganguly et al (2024) Multiple theories 45 Eckstein et al (2015) Jabarzadeh et al (2022) Ju et al (2020) . (2023,) Pereira et al (2021), Feizabadi et al (2019) Relational view 3 Kocoglu et al (2022), Chan and Muthuveloo (2022), Cegarra-Navarro et al .…”
mentioning
confidence: 99%